ChemInform Abstract: Enantioselective Organocatalyzed Domino Synthesis of Six‐Membered Carbocycles. Issue 38 (30th August 2013) - Goudedranche, Sebastien; Raimondi, Wilfried; Bugaut, Xavier; Constantieux, Thierry; Bonne, Damien; Rodriguez, Jean
Abstract Review: ca. 150 refs.